PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI PURI DAJUMA BEACH ECO-RESORT & SPA - Ni Kade Eni Astini; I Made Suwitra Wirya; AA Ratih Wijayanti (Journal of Tourism and Interdiciplinary Studies, 2021)
Puri Dajuma Beach-Eco Resort & SPA is one of the tourism industries that is engaged in resort accommodation and services. This study aims to know partially between the work environment (X1) on employee performance (Y) in Puri Dajuma Beach- Eco Resort & SPA, the partial effect between motivation (X2) on employee performance (Y) at Puri Dajuma Beach-Eco Resort & SP And the simultaneous influence between work environment (X1) and motivation (X2) on employee performance (Y) at Puri Dajuma Beach-Eco Resort & SPA. In this study data collection used a questionnaire distributed to 51 respondents or the number of samples used in this study was 51 people. Processing data in this study using SPSS 22.0 for Windows and Excel software with multiple linear analysis techniques with the results of research that the work environment (X1) partially influences the performance of employees in Puri Dajuma Beach-Eco Resort & SP. The result is t count = 4.171> t table = 2.011 , then for the motivation variable (X2) the result of tcount = 2.483> t table = 2.011 means that the hypothesis is accepted and there is a partial effect between motivation (X2) on employee performance (Y). While based on the F-test, the results of Fcount = 21.086>Ftable = 3.19, means that there is a simultaneous influence between work environment (X1) and motivation (X2) on employee performance (Y) at Puri Dajuma Beach-Eco Resort & SPA.